S. Bernardo dos ventos uivantes: um percurso marxista no calor da luta de classes - Paiva, Kalina Alessandra Rodrigues de (2019)
St. Bernard of the Wuthering Heights: a Marxist course in the heat of the class struggle proposes an essayistic and comparative reading between Emily Brontë's Wuthering Heights and Graciliano Ramos's St. Bernard. Sketched with the Marxist perspective, the thesis highlights the forms of perception of the nineteenth and twentieth centuries, the social mentality and the ideology of their respective times and their aesthetic reflexes in the literary result. Therefore, as a general goal, it studied the literary forms of the novel in the mentioned centuries, analyzing the social space in which the literary works were created, investigating the context, the relation of production and aesthetic as narrative punctuators, observing how the social mentality of these epochs are conditioned by the social relations. Moreover, it confronted the enunciator's time and the enunciation time as strategies for the unfolding of the narratives, in the form of memories, pointing out aesthetic elements as markers of power relations, both reflected in the language and in the structure of the novels, demonstrating, thus, the use of memory as a way of capturing specific time and space and how class relations are experienced, legitimized, and perpetuated. The methodological choices made use of a wide bibliographical research related to the theme, referring to other literary works as a counterpoint, using the dialectical-literary materialistic method, under the sieve of Marxist thought as well as later authors who are linked to Marx through the unfolding of his theorizations. As a result, as an academic contribution, it presents a vision of the private property as a constituent of identities and proposes a concept - of narrative empowerment - that extends to any literary work that has been produced in historical contexts in which there is silence of speech; in which there is a struggle for civil equality; or in which people live in regimes opposed to the democratic State of rights. Bosi, Eagleton, Konder, Marx, Engels, Federici, Löwy, among others, provided the basis for this work.